2019
DOI: 10.1097/jsm.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Effect of Early Aerobic Exercise Treatment for Sport-Related Concussion in Males

Abstract: Objective: To study the effect of early prescribed aerobic exercise versus relative rest on rate of recovery in male adolescents acutely after sport-related concussion (SRC). Design: Quasi-experimental design. Setting: University sports medicine centers. Participants: Exercise group (EG, n = 24, 15.13 ± 1.4 years, 4.75 ± 2.5 days from injury) and rest group (RG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 46 publications
2
93
0
1
Order By: Relevance
“…The review was limited to adolescent athletes (aged 10-19 y), because, historically, this group experiences high rates of SRC and appears to be more vulnerable to prolonged recovery. 1,7 Focused Clinical Question Does subsymptom exacerbation LIAEX within the first 4 weeks following SRC hasten symptom resolution in adolescent athletes?…”
Section: Clinical Scenariomentioning
confidence: 99%
See 3 more Smart Citations
“…The review was limited to adolescent athletes (aged 10-19 y), because, historically, this group experiences high rates of SRC and appears to be more vulnerable to prolonged recovery. 1,7 Focused Clinical Question Does subsymptom exacerbation LIAEX within the first 4 weeks following SRC hasten symptom resolution in adolescent athletes?…”
Section: Clinical Scenariomentioning
confidence: 99%
“…• The literature was searched for studies on the effects of early (within 4 wk) subsymptom exacerbation LIAEX after medically diagnosed SRC in adolescents. • The search yielded 3 articles 2,7,8 that fit inclusion/exclusion criteria. One level 1b randomized controlled trial (RCT), 2 and 1 level 2b nonrandomized trial (NRT) 7 compared LIAEX initiated within 10 days after SRC with usual care (ie, rest).…”
Section: Clinical Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…This growing body of evidence has changed the management of concussions and PCS and the most recent CISG guidelines [21] recommend a short period of rest (24-48 hours) post-injury, followed by a graded return to sub-threshold activity. There have been more studies [106] that have shown the benefits of early sub-threshold aerobic activity in concussion and PCS since guideline came out. A recent randomized controlled trial [107] of over a hundred acutely concussed adolescents showed a significant reduction in recovery time from a median of 17 days in the placebo group to a median of 13 days in the aerobic exercise group (p = 0.006).…”
Section: Treatment Of Pcsmentioning
confidence: 99%